2021
DOI: 10.1111/ped.14604
|View full text |Cite
|
Sign up to set email alerts
|

Diverse actions of cord blood cell therapy for hypoxic‐ischemic encephalopathy

Abstract: Perinatal hypoxic-ischemic encephalopathy (HIE) is a major cause of neonatal death and permanent neurological deficits. However, effective treatments have not yet been established, except therapeutic hypothermia, which is not effective for severe HIE; therefore, developing a novel therapy for HIE is of the utmost importance. Stem cell therapy has recently been identified as a novel therapy for HIE. Among the various stem cell sources, ethical hurdles can be avoided by using stem cells that originate from non-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…The improvement of the area of astrocytes in DG area in HIBD + IN group was more obvious than that in HIBD + IV group. Besides, as previously studied (Sato and Tsuji, 2021), the blow to rats by HIBD also includes inducing neuronal apoptosis. In this study, the number of apoptotic cells in the cerebral cortex and hippocampus of rats decreased signi cantly after stem cell transplantation, indicating that stem cell transplantation can reduce the apoptosis of nerve cells induced by HIBD.…”
Section: Discussionmentioning
confidence: 89%
“…The improvement of the area of astrocytes in DG area in HIBD + IN group was more obvious than that in HIBD + IV group. Besides, as previously studied (Sato and Tsuji, 2021), the blow to rats by HIBD also includes inducing neuronal apoptosis. In this study, the number of apoptotic cells in the cerebral cortex and hippocampus of rats decreased signi cantly after stem cell transplantation, indicating that stem cell transplantation can reduce the apoptosis of nerve cells induced by HIBD.…”
Section: Discussionmentioning
confidence: 89%
“…The improvement of the area of astrocytes in DG area in HIBD+IN group was more obvious than that in HIBD+IV group. Besides, as previously studied [47], the blow to rats by HIBD also includes inducing neuronal apoptosis. In this study, the number of apoptotic cells in the cerebral cortex and hippocampus of rats decreased significantly after stem cell transplantation, indicating that stem cell transplantation can reduce the apoptosis of nerve cells induced by HIBD.…”
Section: The Pathological Changes Of Hibd By Three Huc-mscs Transplan...mentioning
confidence: 89%
“…Previous studies have shown that SCs are less abundant in the brain, intravenously and intraperitoneally [ 58 ]. However, the main therapeutic mechanism of SCs is the production of a variety of cytokines for multi-directional regulation to achieve cascade-like signaling effects so that even a small number of SCs can act as therapeutic agents through the blood–brain barrier [ 57 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. SCs have similar effects on other lesions, which can be explained by their different mechanisms of action in various diseases.…”
Section: Mechanisms Of Sc Therapymentioning
confidence: 99%